ACT and distress tolerance in stroke survivors - A. A. Ovchinnikov; A. N. Sultanova; I. A. Chistyakov (Обозрение психиатрии и медицинской психологии имени В.М. Бехтерева, 2018)
Stroke survivors’ rehabilitation includes physical training and behavioral activation, which associated with pain and discomfort so distress tolerance is important for social adaptation after stroke. We compared effect of ACT and placebo on distress tolerance of 24 patients with cerebrovascular disease. Data analysis showed that 30 min. ACT intervention associated with moderate improving of distress tolerance (F(1,22) = 5.20, p = .03, η^2 = 0.11), effect cannot be explained by changes in negative affect (β = -0.16 [95% C. I. -0.37 - 0.05], p = .13).